Iowa Birdline update, November 7, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for November 7, 1994. Highlights of the update include reports of a growing number of waterfowl and Gulls from all parts of the state as well as many sightings of Western Grebes. Also of note were observations of all three Scoter species, a Long-tailed Duck, and Sandhill Cranes. Also included are handwritten notes for the next week's update with sightings of a Pacific Loon, Tundra Swans, and Golden Eagles. Epson - sheet feed/flatbed